Efficiency measurement of a prototype double dehydrator for candied fruits - Esparaz, Susan T. (1980)
The study was undertaken to determine the efficiency of a prototype double dehydrator for drying candied kalamansi peel. This was accomplished by first standardizing a known procedure of candided kalamansi peel using a cabinet dryer. Adapting the derived procedure for candying, the process was then dried using a double dehydrator. When necessary, drying time and temperature were modified to attain the desired final moisture content of the candied fruit. The laboratory scale procedure of candied kalamansi peel using the double dehydrator was later translated to a scale four times that of the laboratory scale. The candying process briefly involved: debittering ,gradual plumping, coloring through addition of 0.15% food color, and finally drying at 120°F to 140°F in the cabinet dryer. Drying was later done using he two-stage dehydration process instead of just one stage. Results of subjective test revealed that the product most acceptable was dried at 130°F for dry-bulb temperature and 90°F for wet bulb temperature for 3 hours in the first drying stage. The second drying stage involved 2 hours of drying at 150°F. Calibration of the double dehydrator revealed that the dry-bulb temperature reading was 2 to 3 degrees lower than the actual temperature. Fluctuation of temperatures occurred due to low sensitivity of control devices. The double dehydrator was efficient for small scale production and research activities but does not seem to produce good quality product in large scale production.